Adherence of Legionella pneumophila to guinea pig peritoneal macrophages, J774 mouse macrophages, and undifferentiated U937 human monocytes: role of Fc and complement receptors. - Husmann, L K (1992)
Legionella pneumophila, the causative agent of Legionnaires' disease, is a facultative intracellular pathogen of alveolar macrophages. Although previous studies have demonstrated that specific antibody facilitates uptake of L. pneumophila by phagocytic cells, the role of complement has been unclear. Thus, we have examined the relative contributions of Fc gamma- and complement receptor-mediated adherence to guinea pig peritoneal macrophages, U937 human monocytic cells, and J774 mouse macrophage cells. Opsonization of L. pneumophila (Philadelphia 2) with polyclonal immunoglobulin G promoted maximum adherence to guinea pig macrophages. In contrast, incubation in the presence of 20% fresh nonimmune human serum from a single donor did not promote adherence. The results obtained with U937 and J774 cells paralleled those obtained with guinea pig macrophages. In the absence of specific antibody, opsonization with guinea pig complement did not enhance adherence of the Philadelphia 1, Philadelphia 2, or Knoxville strain. However, when complement was added to heat-inactivated, specific antiserum, a fourfold increase in the number of adherent organisms was observed. Blocking studies utilizing membrane receptor-specific monoclonal antibodies demonstrated that both Fc and complement receptors mediated adherence of organisms treated with complement in the presence of specific antibody. These results suggest that complement augments adherence of L. pneumophila only when acting in concert with specific antibody.